2023
DOI: 10.3389/fmicb.2023.1287271
|View full text |Cite
|
Sign up to set email alerts
|

Bacteroides vulgatus alleviates dextran sodium sulfate-induced colitis and depression-like behaviour by facilitating gut-brain axis balance

Xing Wu,
Jiahao Xu,
Jingbo Li
et al.

Abstract: BackgroundPatients with inflammatory bowel disease (IBD) have a higher prevalence of depression. Gut microbiota dysbiosis plays an important role in IBD and depression. However, few studies have explored the characteristic microbiota of patients with IBD and depression (IBDD), or their role in IBDD.MethodsWe performed deep metagenomic sequencing and 16S rDNA quantitative PCR to characterise the gut microbial communities of patients with IBDD and patients with IBD without depression (IBDND). We then assessed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…Wu et al. 's 87 results showed that the faecal foundation of Bacteroides vulgaris ( B. vulgaris ) was lower in patients with IBD than in those with IBDND. Bai et al confirmed that as a common complication of IBD, Clostridium difficile infection (CDI) has been shown to not only exacerbate the symptoms of IBD, but also lead to unexpected outcomes, including death.…”
Section: Resultsmentioning
confidence: 99%
“…Wu et al. 's 87 results showed that the faecal foundation of Bacteroides vulgaris ( B. vulgaris ) was lower in patients with IBD than in those with IBDND. Bai et al confirmed that as a common complication of IBD, Clostridium difficile infection (CDI) has been shown to not only exacerbate the symptoms of IBD, but also lead to unexpected outcomes, including death.…”
Section: Resultsmentioning
confidence: 99%